2019
DOI: 10.5397/cise.2019.22.1.3
|View full text |Cite
|
Sign up to set email alerts
|

The Volume of Subscapularis Muscle Remains Unaffected by Supraspinatus Tendon Tears: Three-dimensionally Reconstructed Magnetic Resonance Imaging Analysis

Abstract: Background: This study aimed to compare the subscapularis muscle volume between the intact groups (group I) and supraspinatus tendon tear groups (group T) based on the sex and three different age groups.Methods: Subjects with a group I and subjects with group T without any other lesions were retrospectively evaluated from among patients who received a magnetic resonance imaging (MRI) scan between January 2011 and December 2013. The MRI scans were studied by a consultant radiologist. The subscapularis muscle vo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Although SSP and SSC tendons are separated by the rotator interval, both tendons are connected by a tendinous cable, the comma tissue. 21,28 Through this structural connection, both tendons seem to affect the stability and biological healing of each other. 8 Hackl et al 14 reported the repaired SSC tendon-stabilizing effect of comma tissue in a biomechanical study.…”
Section: Discussionmentioning
confidence: 99%
“…Although SSP and SSC tendons are separated by the rotator interval, both tendons are connected by a tendinous cable, the comma tissue. 21,28 Through this structural connection, both tendons seem to affect the stability and biological healing of each other. 8 Hackl et al 14 reported the repaired SSC tendon-stabilizing effect of comma tissue in a biomechanical study.…”
Section: Discussionmentioning
confidence: 99%